Desempenho de clones de seringueira da série IAC 300 selecionados para a região noroeste do Estado de São Paulo - Gonçalves, Paulo de Souza; Bortoletto, Nelson; Furtado, Edson Luiz [UNESP]; Sambugaro, Rosana; Bataglia, Ondino Cleante (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2001)
É apresentado o desempenho de 19 novos clones de seringueira [Hevea brasiliensis (Willd. exAdr. de Juss.) Muell. Arg.], resultantes de hibridações conduzidas no Instituto Agronômico e avaliados em experimento de pequena escala, tendo o clone RRIM 600 como testemunha. O experimento em campo obedeceu ao delineamento em blocos ao acaso, com três repetições. Com relação à produção de borracha seca, o clone IAC 40 apresentou a maior média (62,22 g/árvore/sangria) nos três anos de avaliação, seguido pelo IAC 301 (57,67 g/árvore/sangria) e pelo IAC 300 (50,61 g/árvore/sangria), com produções 154%, 138% e 123% superiores em relação ao RRIM 600 (41,04 g/árvore/sangria). Todos os clones selecionados foram vigorosos, com perímetro do caule na abertura do painel variando de 37,81 cm (IAC 317) a 50,90 cm (IAC 315). A porcentagem de plantas aptas a sangria variou de 20,0% (IAC 317) a 100% (IAC 315). Todos os clones apresentaram baixas incidências de quebra pelo vento e de secamento do painel. Não foi detectada nenhuma doença foliar em caráter epidêmico. Dos clones estudados, 15 apresentaram alta resistência à antracnose do painel, e foram superiores ao RRIM 600; os outros cinco apresentaram resistência moderada semelhante ao RRIM 600.

The present paper shows the performance of 19 rubber tree [Hevea brasiliensis (Willd. ex Adr. de Juss.) Muell. Arg.] originated from Hevea breeding programme conducted at the Instituto Agronômico de Campinas (IAC) and evaluated in a small scale trial in the northwestern of São Paulo State, Brazil. The old popular clone RRIM 600 of Malaysian origin was used as control. The trial was laid out in a randomized block design with three replications. Concerned to yielding the clone IAC 40 recorded highest yield (62.22 g/tree/tap) over three years of tapping which was followed by IAC 301 (57.67 g/tree/tap) and IAC 300 (50.61 g/tree/tap) yielding 154%, 138% and 123% superior to the control clone and RRIM 600 whereas recorded 41.04 tree/tap. All selected clones were of vigorous growing, with the girth at opening ranging from 37.81 cm for IAC 317 to 50.90 cm for IAC 315 and tappability ranging from 20.0% for IAC 317 to 100% for IAC 315. All the clones experienced low to very low incidence of wind damage. All selected clones showed low to very low incidence of dry trees. Fifteen clones showed high resistance and five presented moderate resistance to anthrachnose panel canker disease similarly to RRIM 600.
Performance of Hevea clones from IAC 300 series selected in the northwestern region of São Paulo State, Brazil
Keywords: Hevea brasiliensis; características agronômicas; borracha; rendimento; rubber tree; Hevea brasiliensis; agronomic characters; rubber; yields